The Effect of E-Scaffolding in Guided Inquiry Learning on Concept Understanding in Reaction Rate Material - Auliyani, Zaza Fikrati; Rery, R. Usman; Noer, Asmadi M. (Jurnal Penelitian Pendidikan IPA, 2023)
Understanding the concept of an object is needed by students, because the understanding of a concept applies in general so that students can solve more complex problems. This study aims to determine the effect of E-scaffolding in guided inquiry learning on conceptual understanding of reaction rate in class XI IPA MAN 1 Indragiri Hilir E-scaffolding is cognitive assistance in electronic form that given in the guided inquiry learning stage as a cognitive tool to support students. The quasi-experimental research method is used to see the effect of E-scaffolding in guided inquiry learning on conceptual understanding in the control class and the experimental class. The results of the two-way ANOVA hypothesis test with a significance value (0.000) <0.05 indicate that there is a difference in conceptual understanding between the control class and the experimental class. Thus, E-scaffolding can be used as a cognitive assistance for students who have difficulty doing inquiry and cannot be completed independently while in the zone of proximal development (ZPD).